Cumulative contextual risk at birth in relation to adolescent substance use, conduct problems, and risky sex: General and specific predictive associations in a Finnish birth cohort. (July 2016) - Mason, W. Alex; January, Stacy-Ann A.; Chmelka, Mary B.; Parra, Gilbert R.; Savolainen, Jukka; Miettunen, Jouko; Järvelin, Marjo-Riitta; Taanila, Anja; Moilanen, Irma
Abstract: Background: Research indicates that risk factors cluster in the most vulnerable youth, increasing their susceptibility for adverse developmental outcomes. However, most studies of cumulative risk are cross-sectional or short-term longitudinal, and have been based on data from the United States or the United Kingdom. Using data from the Northern Finland Birth Cohort 1986 Study (NFBC1986), we examined cumulative contextual risk (CCR) at birth as a predictor of adolescent substance use and co-occurring conduct problems and risky sex to determine the degree to which CCR predicts specific outcomes over-and-above its effect on general problem behavior, while testing for moderation of associations by gender. Methods: Analyses of survey data from 6963 participants of the NFBC1986 followed from the prenatal/birth period into adolescence were conducted using structural equation modeling. Results: CCR had long-term positive associations with first-order substance use, conduct problems, and risky sex factors, and, in a separate analysis, with a second-order general problem behavior factor. Further analyses showed that there was a positive specific effect of CCR on risky sex, over-and-above general problem behavior, for girls only. Conclusions: This study, conducted within the Finnish context, showed that CCR at birth had long-term general and specific predictive associations with substance use and co-occurring problem behaviors in adolescence; effects on risky sex were stronger for girls. Results are consistent with the hypothesis that early exposure to CCR can have lasting adverse consequences, suggesting the need for early identification and intervention efforts for vulnerable children. Highlights: Cumulative Contextual Risk (CCR) at birth had long-term consequences for teens. CCR predicted substance misuse, conduct problems, and risky sex over the long term. CCR also had a long-term predictive association with general problem behavior. CCR had a specific predictive association with risky sex for girls but not boys. The study, conducted in Finland, extends prior research conducted in the US and UK.